Shame and the anti-feminist backlash : Britain, Ireland and Australia, 1890-1920 - Crozier-De Rosa, Sharon (Routledge research in gender and history, 2018)
"This book places the concept of shame within a historical context. It examines how this emotion was used by popular writers (especially female writers) in the widespread backlash against feminism at the end of the nineteenth and beginning of the twentieth century, in Britain, Ireland and Australia. Shame was considered to be an overwhelmingly appropriate weapon in the campaign against the aspirations and actions of the 'unwomanly' woman. Trouble arose, however, when it appeared that these unwomanly women were either resistant to or incapable of experiencing this highly gendered emotion.This study casts new light on just how intricately shame was linked with anxieties about the future of civilisation, and therefore with feminism, imperialism, nationalism, in the popular mentality of those inhabiting regions of the British Empire. The book examines the far-reaching implications feminism had for nation and empire, and uncovers the extent to which shame and shaming was relied on as a tool for social control among female writers of anti-feminist persuasion."--Provided by publisher.